Populist Attitudes and Voting: Does Populist Voters vote for New Political Parties? (The Case of 2016 Seimas Elections?) - Skirkevičius, Paulius (Politologija, 2022)
Concerming the success of new/renewed political parties in Lithuania, quite often they are labelled as populist ones .This article seeks to answer the question – do populist attitudes of individuals could be variables that explains voting for new political parties? Firstly, we analyze the structure of populist attitudes in Lithunia. The analysis using attitudes measures suggested by CSES revealed that these attitudes fits theorectical expectations quite well. Two dimensions of populist attitudes can be distinguished – anti-elitism and the one concerning peoples role in politics. Futher analysis of electoral behavior, that populist attitudes does not explain voting for the new political party, other variables such as political support/trust does explain it better. However the analysis is limited to one elections and one political party, so the conclusions should be considered with caution and further analysis is needed.
Keywords: New parties; populism; electoral behaviour